2016
DOI: 10.1136/archdischild-2015-310165
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing infection in neonatal intensive care units through quality improvement

Abstract: This study demonstrates a >50% reduction in BSI in extremely premature neonates from D3 to 35 following a collaborative quality improvement project to reduce neonatal infection across an NICU network, supported by timely provision of data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 26 publications
0
37
0
1
Order By: Relevance
“…Çünkü bu bebeklerde immün sistem yeterince gelişmemiştir. Ayrıca invaziv girişimlerin sık uygulanmasıda sağlık bakım ilişkili enfeksiyon (SBİE)'ların sıklığını yükseltir (3,4). SBİE'ler bu bebekler için önemli bir morbidite ve mortalite nedeni olup hastanede kalış süresini ve maliyetleri arttırır (3,5,6).…”
Section: Introductionunclassified
“…Çünkü bu bebeklerde immün sistem yeterince gelişmemiştir. Ayrıca invaziv girişimlerin sık uygulanmasıda sağlık bakım ilişkili enfeksiyon (SBİE)'ların sıklığını yükseltir (3,4). SBİE'ler bu bebekler için önemli bir morbidite ve mortalite nedeni olup hastanede kalış süresini ve maliyetleri arttırır (3,5,6).…”
Section: Introductionunclassified
“…The risk of CLABSI is significantly increased in patients with lower gestational age and birth weight, as they exhibit poor skin integrity, an immature immune system, and require the prolonged use of central lines [ 6 ]. As a result, CLABSI are the most common cause of late onset sepsis (LOS) in neonates and thus constitute one of the leading causes of both morbidity and mortality in this age group [ 7 ]. The Australian and New Zealand Neonatal Network (ANZNN) reports the incidence of late onset sepsis as 4.5%, with CLABSI constituting 69% of these infections [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of CLABSI at The Canberra Hospital (TCH) in 2012-2013 showed one of the highest rates among each of the NICUs in New South Wales and the Australian Capital Territory [ 7 ]. In response, current practices were audited and a new central line bundle policy was introduced in 2014 in attempt to lower this statistic.…”
Section: Introductionmentioning
confidence: 99%
“…The proven quality improvement initiatives to improve the neonatal care outcomes include maintaining hand hygiene, maintenance and optimization of the central line, improving mother-infant interaction, reducing the risk of bronchopulmonary dysplasia and hypothermia, reducing the exposure of infants to various stressors, and implementing the family-centered care approach. Pain assessment and management Pain assessment and documentation using a neonatal pain tool, N-PASS Considerable improvement in pain reduction strategies -2 Ting et al 9 CLABSI prevention 10 step regimen Considerable reduction in rate of CLABSI Bowen et al 11 Koeppel et al 12 Zhou et al 14 Byrd et al 15 3…”
Section: Discussionmentioning
confidence: 99%
“…Bowden et al 11 in 2011 demonstrate a >50% reduction in BSI in extremely premature neonates from D3 to 35 following a collaborative quality improvement project to reduce neonatal infection across a NICU network consisting of eight neonatal intensive care units (NICUs) in New South Wales, Australia. Koeppel et al, 12 on a 10year review of CLABSI prevention efforts in NICUs, demonstrated that the implementation of QI processes that include strict compliance to best practices and decreasing central line entry by use of a closedmedication system were associated with a significant and sustainable reduction in CLABSI rates.…”
Section: Prevention Of Sepsismentioning
confidence: 99%